Color stability of esthetic restorative materials: a spectrophotometric analysis. Issue 1 (1st January 2016) - Poggio, Claudio; Ceci, Matteo; Beltrami, Riccardo; Mirando, Maria; Wassim, Jaffal; Colombo, Marco
Abstract: Objective: The aim of this in vitro study was to evaluate the color stability of different restorative materials (one microfilled composite, one nanofilled composite, one nanohybrid composite and one Ormocer-based composite) after exposure to different staining solutions (coffee, coca-cola and red wine). Material and methods: All materials were polymerized into silicon rings (2 mm ×6 mm ×8 mm) to obtain specimens identical in size. Thirty cylindrical specimens of each material were prepared. They were immersed in staining solutions over a 28-day test period. A colorimetric evaluation according to the CIE L*a*b* system was performed by a blind trained operator at 7, 14, 21, 28 days of the staining process. The Shapiro–Wilk test and Kruskal–Wallis ANOVA were applied to assess significant differences among restorative materials. The paired t -test was applied to test which CIE L*a*b* parameters significantly changed after immersion in staining solutions. Results: All restorative materials showed clinically perceptible color differences after immersion in coffee. L* and b* values showed the highest variability. Coca cola and red wine did not influence the color stability for all restorative materials except for Filtek Supreme XTE. Conclusions: Coffee caused a significant color change in all types of tested composite resins. Filtek Supreme XTE demonstrated alone a staining susceptibility to red wine; no other significant differences among the materials were demonstrated. Long-term exposure to some food dyes (coffee in particular) can significantly affect the color stability of modern esthetic restorative materials regardless of materials' different composition.